Low-dose multidetector computed tomography of the cervical spine: optimization of iterative reconstruction strength levels. (April 2014) - Omoumi, Patrick; Verdun, Francis R; Salah, Yosr Ben; Berg, Bruno C Vande; Lecouvet, Frederic E; Malghem, Jacques; Ott, Julien G; Meuli, Reto; Becce, Fabio
Background: Iterative reconstruction (IR) techniques reduce image noise in multidetector computed tomography (MDCT) imaging. They can therefore be used to reduce radiation dose while maintaining diagnostic image quality nearly constant. However, CT manufacturers offer several strength levels of IR to choose from. Purpose: To determine the optimal strength level of IR in low-dose MDCT of the cervical spine. Material and Methods: Thirty consecutive patients investigated by low-dose cervical spine MDCT were prospectively studied. Raw data were reconstructed using filtered back-projection and sinogram-affirmed IR (SAFIRE, strength levels 1 to 5) techniques. Image noise, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) were measured at C3–C4 and C6–C7 levels. Two radiologists independently and blindly evaluated various anatomical structures (both dense and soft tissues) using a 4-point scale. They also rated the overall diagnostic image quality using a 10-point scale. Results: As IR strength levels increased, image noise decreased linearly, while SNR and CNR both increased linearly at C3–C4 and C6–C7 levels ( P  < 0.001). For the intervertebral discs, the content of neural foramina and dural sac, and for the ligaments, subjective image quality scores increased linearly with increasing IR strength level ( P  ≤ 0.03). Conversely, for the soft tissues and trabecular bone, the scores decreased linearly with increasing IR strength level ( P  < 0.001). Finally, the overall diagnostic image quality scores increased linearly with increasing IR strength level ( P  < 0.001). Conclusion: The optimal strength level of IR in low-dose cervical spine MDCT depends on the anatomical structure to be analyzed. For the intervertebral discs and the content of neural foramina, high strength levels of IR are recommended.